Prognostic cancer gene expression signatures: current status and challenges - Qian, Yuquan; Daza Barragán, Jimmy Andres; Itzel, Timo; Betge, Johannes; Zhan, Tianzuo; Marmé, Frederik; Teufel, Andreas (Cells, 2021)
Current staging systems of cancer are mainly based on the anatomical extent of disease. They need refinement by biological parameters to improve stratification of patients for tumor therapy or surveillance strategies. Thanks to developments in genomic, transcriptomic, and big-data technologies, we are now able to explore molecular characteristics of tumors in detail and determine their clinical relevance. This has led to numerous prognostic and predictive gene expression signatures that have the potential to establish a classification of tumor subgroups by biological determinants. However, only a few gene signatures have reached the stage of clinical implementation so far. In this review article, we summarize the current status, and present and future challenges of prognostic gene signatures in three relevant cancer entities: breast cancer, colorectal cancer, and hepatocellular carcinoma.
Gesehen am 27.07.2021